Prevalence of mental illness among old age people in urban area: A study in Kolkata, West Bengal - Chakraborty, Abhijit; Mandal, Aloke Kumar; Mukhopadhyay, Debshankar; Ghosh, Srijit (Asian Journal of Medical Sciences, 2022)
Background: With an increasing life expectancy, the population of geriatric age group is increasing in India and all around the world. The population aged above 60 years is 8% as per census 2011 and likely to be 21% of the total population by 2050. People from older age group suffer from mental problems more than their younger counterparts. Few studies have targeted the mental health of elderly in community level, especially in Bengal. Aims and Objectives: This study aims to estimate the prevalence of mental illness among older age group of urban area in Kolkata, West Bengal. Materials and Methods: This cross-sectional, descriptive, epidemiological community-based study was conducted in the Chetla area of Kolkata Municipal Corporation, West Bengal. The General Health Questionnaire-12 (GHQ-12) and Mini-Mental State Examination were administered to 341 participants. Results: We found 36.95% of old age people having mental illness based on GHQ-12. Females have more prevalence of having a psychiatric illness than males. The most common psychiatric disorder was mood disorder followed by dementia. The prevalence of mental illness increased with advancement of age. About 64.7% of people never sought any kind of treatment for their illness. Conclusion: Mental illness is common among elderly people, but they are not well documented. A very significant number of patients do no seek any kind of treatment for their ailments. A comprehensive health-care system to be developed to reduce this treatment gap.